AI LITERACY AND RISK TOLERANCE AMONG UNIVERSITY STUDENTS - Dwi Fitra Arreski; Fadhilah Ahmad Qaniah; Maharani Eka (IDEI: Jurnal Ekonomi & Bisnis (IDEI: Journal of Economics & Business), 2026)
This study investigated the relationship between artificial intelligence (AI) literacy and risk tolerance among Indonesian university students. As generative AI tools became deeply embedded in students' academic and personal decision-making, understanding how different dimensions of AI literacy related to risk-taking dispositions became increasingly important. A correlational quantitative design was employed, involving 156 university students recruited through purposive sampling. AI literacy was measured using the seven-dimensional AI Literacy Scale developed by Nong et al. (2024), comprising application ability, morality, critical thinking, self-efficacy, cognitive ability, perceived ease of use, and perceived usefulness. Risk tolerance was assessed using the Financial Risk Tolerance Scale developed by Grable and Lytton (1999). Spearman's rho correlation analysis was used to examine the relationship between variables. The results revealed that only the perceived ease of use dimension was significantly and negatively correlated with risk tolerance (r = -0.326, p < 0.01), whereas the other six dimensions of AI literacy showed no significant correlation. These findings indicated that students who perceived AI tools as easier to use tended to display lower risk tolerance, suggesting that effortless interaction with AI may foster cognitive comfort that reduces willingness to engage with uncertainty. The study contributed to the AI literacy literature by demonstrating dimension-specific associations between AI literacy and a key psychological disposition. Penelitian ini menyelidiki hubungan antara literasi kecerdasan buatan (AI) dan toleransi risiko pada mahasiswa di Indonesia. Seiring dengan semakin tertanamnya alat AI generatif dalam pengambilan keputusan akademik dan personal mahasiswa, pemahaman tentang bagaimana berbagai dimensi literasi AI berkaitan dengan disposisi pengambilan risiko menjadi semakin penting. Penelitian ini menggunakan desain kuantitatif korelasional dengan melibatkan 156 mahasiswa yang dipilih melalui purposive sampling. Literasi AI diukur menggunakan AI Literacy Scale tujuh dimensi yang dikembangkan oleh Nong et al. (2024), terdiri dari application ability, morality, critical thinking, self-efficacy, cognitive ability, perceived ease of use, dan perceived usefulness. Toleransi risiko diukur menggunakan Financial Risk Tolerance Scale yang dikembangkan oleh Grable dan Lytton (1999). Analisis korelasi Spearman digunakan untuk menguji hubungan antar variabel. Hasil penelitian menunjukkan bahwa hanya dimensi perceived ease of use yang berkorelasi negatif signifikan dengan toleransi risiko (r = -0,234, p < 0,01), sedangkan enam dimensi literasi AI lainnya tidak berkorelasi signifikan. Temuan ini mengindikasikan bahwa mahasiswa yang merasa alat AI lebih mudah digunakan cenderung memiliki toleransi risiko yang lebih rendah, menunjukkan bahwa interaksi yang mudah dengan AI dapat menumbuhkan kenyamanan kognitif yang menurunkan kesediaan menghadapi ketidakpastian.